Visionary Women and Visible Children, England 1900-1920 Childhood and the Women's Movement - Mayall, Berry (Springer International Publishing, 2018)
This book addresses the inter-linked lives and fortunes of children and women in the first two decades of the twentieth century in England. This was a time of shifts in thinking and practice about children's and women's status, lived lives and experiences. The book provides a detailed explanation of how children experienced home, neighbourhood and elementary school; as well as discussing the impact of the women's movement, namely its suffrage and socialist work. These two concerns are linked by the work women did about and for children. Essentially, the book explores childhood and womanhood; generation and gender; and socialism and feminism. Using existing studies on women's work, and autobiographies and interviews about childhood, Mayall argues that women played a large part in re-thinking childhood as a special period in life, and children as participants in learning and in politics. This book will appeal to students and researchers in the fields of history, education and sociology, particularly those interested in the women's movement, and the history of childhood. .